Relação entre poluição do ar e internações de idosos por infarto agudo do miocárdio no Município de São Paulo entre 2000 a 2012. - Oliveira, David Aguiar de (2015)
Introduction: In public health, the issue of environmental pollution due to its consequences on people's health, is considered a problem and a challenge to be faced by all. Levels of pollutants released in the atmosphere by cars, industries and the burning of forests, pastures and products such as sugarcane, cause pollution levels harmful to health, especially of vulnerable groups such as children and the elderly. In São Paulo cardiovascular problems and especially the acute myocardial infarction (IAM) has affected the health of the elderly, those related to environmental pollution. Objective: To evaluate the relationship between air pollution and hospital admissions of elderly by Acute Myocardial Infarction (AMI) in the municipality of São Paulo from 2000 to 2012, noting its lag structure. Methods: It is an ecological time-series study. Data on PM10, CO, SO2, NO2 and O3 as well as temperatures and relative humidity were collected from the Environmental Sanitation Technology Company of the State of São Paulo ¿ CETESB. Data on hospital admissions were obtained from the National Health System Database - SUS (DATASUS). Hospital admissions for acute myocardial infarction (AMI - ICD 10: I21). Descriptive analysis was made using the Pearson correlation. The relationship between air pollution and MI was evaluated using a polynomial model delay distribution with up to 6 days after exposure to the pollutant. Were also used linear models Poisson generalizations, controlling for long-term seasonality, day of week, temperature and humidity. It was made in calculating the number of admissions to interquartile difference of significant pollutants in the regression model. The 5% significance level was used. Results: Were hospitalize d for AMI in the SUS from 2000 to 2012, 39.783 patients, of whom 22.832 were male (57.4%) and 16.951women (42.6%). The five pollutants analyzed in São Paulo, only the O3 did not show a statistically significant acute effect on the outcome and age group. The PM10, SO2, NO2 , CO, acute and showed statistically significant effects. For the increase of one interquartile (24,42¿g/m3) of PM10, there was an increase in total AMI hospitalizations for seniors in 2.77% (95% CI: 0.93 to 4.61). For female admissions, there is a sharp and statistically significant effect on exposure and on the first day after exposure. For the increase of one interquartile (24,42¿g/m3) of PM10, there was an increase in the number of admissions to 5.02% (95% CI: 2.28 to 7.77). For admissions male, is not observed acute effect. For the increase of one interquartile (7,48¿g/m3) of SO2, there was an increase in total AMI hospitalizations for seniors in 2.86% (95% CI: 0.97 to 4.75). For female admissions, there is a sharp and statistically significant effect on exposure and on the first day after exposure. For the increase of one interquartile (51.89ug/m3) of NO2, there was an increase in total AMI hospitalizations for seniors in 2.04% (95% CI: 0.27 to 3.80). For female admissions , we observe a sharp and statistically significant effect on exposure day. With increase of one interquartile (51,89¿g/m3) of NO2, there was an increase in the number of admissions to 0.02 to 5.30% (95% CI: 1.03 to 6.65). For admissions male, is not observed acute effect. For the increase of one interquartile (1,33¿g/m3) of CO, there was an increase in total AMI hospitalizations for seniors in 1.95% (95% CI: 0.31 to 3.58). For female admissions, there is a sharp and statistically significant effect on exposure day. For the increase of one interquartile (1,33¿g/m3) of CO, there was an increase in the number of admissions to 3.83 % (95% CI: 1.39 to 6.26 ). For admissions male, is not observed acute effect. Conclusion: There is a relationship between air pollution and the IAM, and among older women are most affected. It is necessary to continue close monitoring of pollutants.